Penggolongan Obat Berdasarkan Peresepan Obat Asma Di Instalasi Rawat Jalan RSUD Dr Agoesdjam Ketapang - Defiga Kasrin; Liza Pratiwi; Shoma Rizkifani (Journal Syifa Sciences and Clinical Research, 2022)
Asthma was included in the top ten causes of morbidity and mortality in Indonesia. The priority of asthma treatment so far is to control symptoms. Therefore, the classification of drugs based on asthma drug prescribing is very necessary. This study aims to determine the characteristics and classes of drug prescribing in outpatient asthma patients at RSUD Dr. Agoesdjam Ketapang in 2020. This research method was carried out in December 2021-January 2022 with a retrospective descriptive method, data obtained from medical record cards of outpatient asthma patients at RSUD Dr. Agoesdjam Ketapang in 2020. The data obtained are presented in the form of percentages, average values and tables. The results showed that of the 61 outpatient asthma patient medical records analyzed by the percentage data, the majority of patients were women (59%) and at the age of 42-49 years (31%). The most widely prescribed drug group was beta-2 agonist (48%) with the most common dosage form being inhalers (51%) and the route of drug use was inhalation (51%). The conclusion is that the use of drugs in asthma patients in the outpatient installation of RSUD Dr. The majority of Agoesdjam Ketapang are women. The majority occurred at the age of 42-49 years, the most widely used drug class was the beta-2 agonist group with the inhaler dosage form and the inhalation route was the most widely used.